Pengaruh Komposisi Media Tanam Yang diberi Eco Enzym Terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) - Nerty Soverda; Elly Indra Swari; Neliyati Neliyati (Jurnal Media Pertanian, 2023)
The shallot plant (Allium ascalonicum L.) is a horticultural plant, which spreads both in hot (tropical) and temperate (sub-tropical) climates. One of the problems in managing the cultivation is the condition of the land which is dominated by ultisols with low fertility. The purpose of this study was to study the effect of the composition of the planting medium which was given eco enzymes on the growth and yield of shallot (Allium ascalonicum L.) plants. This research was conducted at the Teaching and Research Farm, Faculty of Agriculture, Jambi University, Mendalo Village, Jambi Luar Kota District, Muaro Jambi Regency, Jambi Province. The research design used was a randomized block design (RBD) with planting media treated with and without eco enzymes with the treatment stages, namely M1 = soil without eco enzyme watering, M2 = soil + eco enzyme watering, M3 = soil + manure without watering eco enzymes, M4 = soil + manure + watered with eco enzymes, M5 = soil + manure + roasted husks without eco enzymes watered and M6 = soil + manure + roasted husks + watered with eco enzymes. The observed variables were plant height, number of leaves, number of tubers per hill and tuber weight per hill. The results showed that the use of planting media of goat manure and husk charcoal supplemented with eco enzymes could increase the value of plant height, number of leaves, number of tubers per hill and tuber weight per hill of Brebes shallot varieties. The treatment that gave the best results was goat manure + husk charcoal + eco enzyme.